Medical geology and overview of studies from Africa and Asia - Aliyu Ahmad Warra; Atiqah Binti Ab Aziz; Tunku Kamarul Zaman Tunku Zainol Abidin (CABI, 2023)
Abstract Despite some appreciable development of Medical Geology reported in various parts of the world, Africa and Asia are still developing. Indeed, there is substantial evidence to demonstrate that research in this area holds significant relevance for the African and Asian continents. Given the importance of geo-environmental materials, factors, and processes, including both geogenic and anthropogenic activities, as well as the consistently reported cases of diseases associated with such activities in Africa and Asia, it has become imperative to explore genuine relationships. This review delves into comprehensive studies on the impact of geological factors on human health. The geologic sources of contamination by toxic elements in the environment, which lead to human exposure through food and water, are examined closely. Recent case studies, research, and development (R&D) efforts undertaken by scholars, researchers, and government institutions are also thoroughly reviewed, with the aim of charting a course toward viable solutions. Furthermore, the discussion extends to raising awareness about the harmful effects of water contamination caused by toxic metals, such as arsenic and fluoride, and addressing mining hazards in Africa and Asia. The issue of exposure to toxic metals and metalloids, including lead and chromium (II), is also tackled. Recommendations are put forth emphasizing the necessity of synergy among medical scientists, geologists, geochemists, biochemists, and other stakeholders involved in environmental health studies. The importance of creating an environment conducive to brainstorming ideas that contribute to understanding the emergence of new pathologies, as well as the development of pertinent curricula for institutions in Africa and Asia, is also thoroughly discussed.